Forging Neuroimaging Targets for Recovery in Opioid Use Disorder - Stewart, Jennifer L.; May, April C.; Aupperle, Robin L.; Bodurka, Jerzy (Frontiers in Psychiatry, 2019)
Many individuals with opioid use disorder (OUD) consume drugs to relieve physical and/or emotional pain, a pattern that may increasingly result in death. The field of addiction research lacks a comprehensive understanding of physiological and neural mechanisms instantiating this cycle of Negative Reinforcement in OUD, resulting in limited interventions that successfully promote abstinence and recovery. The Three-Stage Model of Addiction underscores Negative Reinforcement processes as crucial to the maintenance and exacerbation of chronic substance use together with Binge/Intoxication and Preoccupation/Anticipation processes. The present review highlights faulty brain circuitry and processes associated with OUD within the context of this three-stage model, focusing on cross-sectional as well as longitudinal studies of relapse and treatment outcome that employ magnetic resonance imaging (MRI), functional near-infrared spectroscopy (fNIRs), and/or electroencephalography (EEG) explored in frequency and time domains (the latter measured by event-related potentials, or ERPs). We discuss strengths and limitations of this neuroimaging work with respect to study design and individual differences that may influence interpretation of findings (e.g., opioid use chronicity/recency, comorbid symptoms, and biological sex). Lastly, we translate gaps in the OUD literature, particularly with respect to Negative Reinforcement processes, into future research directions involving operant and classical conditioning involving aversion/stress. Overall, our analysis of the literature suggests that opioid-related stimuli may lessen their hold on frontocingulate mechanisms implicated in Preoccupation/Anticipation as a function of prolonged abstinence, and that degree of frontocingulate impairment may predict treatment outcome, although longitudinal research is warranted to replicate these findings. We remain hopeful that a neuroscience-informed understanding of individual differences will elucidate potential targets for OUD intervention.